Towards the Global Vision of Engagement of Generation Z at the Workplace: Mathematical Modeling - Radoslaw A. KYCIA; Agnieszka NIEMCZYNOWICZ; Joanna NIEZURAWSKA-ZAJAC (Communications of International Proceedings, 2021)
Correlation and cluster analyses (k-Means, Gaussian Mixture Models) were performed on Generation Z engagement surveys at the workplace. The clustering indicates relations between various factors that describe the engagement of employees. The most noticeable factors are a clear statement about the responsibilities at work, and challenging work. These factors are essential in practice. The results of this paper can be used in preparing better motivational systems aimed at Generation Z employees.
Keywords: Employee Engagement; Generation Z; Mathematical Modelling; Principal Component Analysis; Gaussian Mixture Model; k-Means Clustering